Penerapan Wasiat Wajibah Terhadap Ahli Waris Non Muslim Dari Prespektif Kompilasi Hukum Islam (KHI) (Suatu Analisis Dari Putusan Mahkamah Agung Nomor. 331/K/Ag/2018/MA) - Liana Noviyanti (LPPM Universitas Ekasakti Padang, 2023)
A mandatory will is a will intended for heirs or relatives who do not receive a share of the inheritance from the testator given by the judge, Islamic law has stated that people of different religions cannot inherit from each other, whether Muslims inherit from non-Muslims or non-Muslims inherit from Muslims, but in practice mandatory wills are currently implemented as an alternative to several inheritance problems such as the right to inheritance of assets for heirs of different religions, children and adoptive parents. Judges at the Supreme Court level apply mandatory wills, taking into account the sense of justice and humanity for heirs who are prevented from inheriting as stated in Supreme Court Decision Number. 331/K/AG/2018/MA. This research aims to examine how the mandatory will is implemented for heirs who change beliefs after the death of the testator in the Supreme Court decision Number. 331/K/AG/2018/MA based on the provisions of the Compilation of Islamic Law (KHI), this research is normative legal research which is known as research for academic purposes. namely the process of searching for legal rules, legal doctrines, and legal principles to answer the legal issues being discussed.